South Africa - Country Procurement Assessment Report : Refining the Public Procurement System, Volume 2. Main Text - World Bank (Washington, DC, 2013)
This reports examines the importance of efficient public procurement for the national economy for South Africa. The country faces a unique task of merging a dual economy consisting of the exiting "main stream economy" and, an "emerging economy". To provide a national environment for optimal economic development; the government planned to mold the two economies into a sustainable unified growth pattern. Following are main recommendations for the near term. A national uniform procurement policy is currently being put in place, which will be applicable to all organs of state. Preparation of a draft for a national legislative/regulatory framework for public procurement to establish uniformity in tender procedures, policies and control measures. Creation of a national procurement compliance office in the National Treasury, which would be responsible only for procurement policy formulation, laws and procedures, provisions of standard bidding documents and contracts, oversight on implementation by all organs of state, establishment of a procurement data capturing system, and training of procurement staff. Decision implementation to abolish the Tender Boards and have their functions assumed by the responsible organs of state at the national, provincial, and local levels. Establish under the National Public Housing Scheme a competitive procedure for the award of contracts development to obtain savings in the expenditure of fiscal revenues. Abolish the industrial participation program which conflicts with the basic principles of efficient, fair, and transparent procurement. Revise the preferential procurement regulations to provide for "graduation" of previously disadvantaged enterprises when they have reached a certain turn over rate to avoid that only an elite group continues to benefit from the system.